ECONOMIC EMPOWERMENT OF WOMEN THROUH SELF HELP GROUPS IN KERALA - REJI (International Journal of Marketing, Financial Services & Management Research, 2013)
The empowerment of women is crucial for the development of the country. Bringing women into the main stream of development is major concern for the Government of India. That is why the year 2001 has been declared as the “Year of women Empowerment” Women’s empowerment is critical to the socio economic progress of the community and bringing women into the main stream of national development has, therefore, been a major concern of the government. The Ministry of Rural Development has special components for women in its programmes and funds are “women component” to ensure flow of adequate resources for the same. One of the major schemes implemented by the Ministry of Rural Development having women’s component is the SGSY.